Characterization of Lysinibacillus spp. (Strain G6) for hydrolysing porcine gelatine - Rul Aisyah Mat Repin,; Safiyyah Shahimi,; Mohd Fadly Lamri,; Maaruf Abdul Ghani,; Sahilah Abd. Mutalib, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was conducted to identify and characterize gelatinase bacterium of Lysinibacillus spp. (Strain G6) for hydrolysing porcine gelatine. The Strain G6 colony was chosen due to its high ability to hydrolyse porcine gelatine when it was grown on medium containing porcine gelatine by forming a clear zone. The bacterium was identified as Lysinibacillus spp. Strain G6 using the partial sequence of 16S rDNA analysis with 95% of similarity. Meanwhile, by using Biolog GEN III, the bacterium strain was identified as Lysinibacillus sphaericus analysis at 42% of similarity. Gelatinase from the bacterium has been partially purified using deposition of ammonium sulphate and tube dialysis. The partially purified gelatinase of Strain G6 showed significant different (p<0.05) in porcine gelatinase activity of 9.12a ± 2.6 U/ml followed by bovine (5.43b ± 0.8 U/ ml) and fish gelatine (0.14c ± 0.7 U/ml). The molecular weight of gelatinase of Strain G6 was 123.35 kDa. Application of partially purified gelatinase onto porcine, bovine and fish capsules substituted into the gelatin medium (GM), respectively resulted in 11.86a ± 0.2 U/ml, 5.39b ± 2.1 U/ml and 0.36c ± 0.2 U/ml of enzyme activity, respectively. Thus, Lysinibacillus spp. Strain G6 bacterium showed greatest gelatinase activity towards porcine gelatine which can be potentially used for porcine gelatine identification.